Role of Uric Acid as a Biomarker for Predicting Coronary Angiographic Severity in Acute Coronary Syndrome Patients - Kalyani, Alok Kumar (Journal of Biomedical and Pharmaceutical Research, 2018)
Uric acid, a by-product of purine metabolism, has emerged as a potential biomarker for predicting cardiovascular disease severity, particularly in patients with Acute Coronary Syndrome (ACS). This study aims to evaluate the role of uric acid levels in predicting the severity of coronary artery disease (CAD) as determined by coronary angiography in ACS patients. A total of 150 patients diagnosed with ACS were included in the study. Serum uric acid levels were measured upon admission, and coronary angiography was performed to assess the severity of CAD using the Gensini score. The results showed a significant positive correlation between elevated uric acid levels and higher Gensini scores, indicating more severe coronary artery involvement. Uric acid levels were found to be an independent predictor of CAD severity, with a sensitivity of 75% and specificity of 70%. These findings suggest that uric acid could be used as a cost-effective and easily available biomarker to predict coronary artery disease severity in ACS patients, potentially aiding early clinical decision-making. Keywords: Uric acid, biomarker, Acute Coronary Syndrome, coronary angiography, Gensini score, coronary artery disease.